2018
DOI: 10.3390/ijms19061609
|View full text |Cite
|
Sign up to set email alerts
|

Ru(II)-Thymine Complex Causes Cell Growth Inhibition and Induction of Caspase-Mediated Apoptosis in Human Promyelocytic Leukemia HL-60 Cells

Abstract: Ruthenium-based compounds represent a class of potential antineoplastic drugs. Recently, we designed, synthesized, and identified the Ru(II)-thymine complex [Ru(PPh3)2(Thy)(bipy)]PF6 (where PPh = triphenylphosphine, Thy = thymine and bipy = 2,2′-bipyridine) as a potent cytotoxic agent with the ability to bind to DNA and human and bovine serum albumins. In this study, the underlying cytotoxic mechanism of the [Ru(PPh3)2(Thy)(bipy)]PF6 complex was assessed. This complex displayed potent cytotoxicity in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 29 publications
0
11
0
1
Order By: Relevance
“…In this sense, the knowledge of molecular and biochemical mechanisms is of great relevance 3 . The probable mechanisms of action of many recently described ruthenium complexes involve apoptosis 27,32,[36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the knowledge of molecular and biochemical mechanisms is of great relevance 3 . The probable mechanisms of action of many recently described ruthenium complexes involve apoptosis 27,32,[36][37][38] .…”
Section: Resultsmentioning
confidence: 99%
“…www.nature.com/scientificreports/DiscussionRuthenium complexes have been extensively explored in recent years mainly due to their antitumor[26][27][28][29] and antiparasitic activities. Some studies of our research group have investigated the cytotoxic potential of different ruthenium complexes against parasites of the Leishmania genus10,30 (Costa et al, 2017;Miranda et al, 2018), and we have also demonstrated the probable cell death mechanism triggered by ruthenium complex called 3-hydroxy-4-methoxybenzoate (hmxbato)-cis-[Ru II (ŋ 2 -O 2 CC 7 H 7 O 2 )(dppm) 2 ]PF 6 against Leishmania (Leishmania) amazonensis promastigotes…”
mentioning
confidence: 99%
“…In a new set of experiment, human promyelocytic leukemia HL-60 cell line was used as a cellular model, since it was among the most sensitive cell lines to the complex tested. Moreover, this cell line is often used as cellular model in the study of the mechanism of action of new compounds [5] , [28] , [47] , [48] . Therefore, the cytotoxicity of the complex was confirmed by TBE assay in HL-60 cells after 24 and 48 h of incubation.…”
Section: Resultsmentioning
confidence: 99%
“…The design of metallodrug-based compounds is an interesting strategy in medicinal chemistry [24] , [25] , [26] , [27] , [28] , [29] , [30] . The most important metallodrug-based compounds are the platinum-based antineoplastic agents.…”
Section: Introductionmentioning
confidence: 99%
“…Além da apoptose, outro tipo de morte celular encontrada é a autofagia, que pode ser ativada principalmente em situações que envolvam estresse celular (SMIRLIS et al, 2010 Vários estudos tem demonstrado que a ação dos complexos de rutênio contra células tumoral envolve a indução da morte celular por apoptose (HUANG et al, 2018;JIANG et al, 2019a;PETTINARI et al, 2014;TANG et al, 2019;YU et al, 2014 Os complexos de rutênio vêm sendo extensivamente explorados nos últimos anos, sobretudo devido as suas atividades antitumorais (CARNIZELLO et al, 2016;DE SOUZA OLIVEIRA et al, 2018;DÖMÖTÖR et al, 2017;QIN et al, 2019;SILVA et al, 2018) e antiparasitárias (COSTA et al, 2017MIRANDA et al, 2018;NASCIMENTO et al, 2019). Nosso grupo de pesquisa tem demonstrado o potencial citotóxico de diferentes complexos de rutênio contra parasitos do gênero Leishmania (COSTA et al, 2017;MIRANDA et al, 2018 (CHEN et al, 2019;DABIRI et al, 2018;DE SOUZA OLIVEIRA et al, 2018;LU et al, 2016;WAN et al, 2017).…”
Section: Discussionunclassified